Mediation as an Effort to Resolve Disputes on Ownership and Control of Heirs' Land - Norafiq Aldyan; Dian Latifiani; Nur Arif Nugraha (Journal of Private and Commercial Law, 2024)
Support the successful implementation of mediation. This research uses a juridical-empirical approach. Data sources come from primary and secondary data using interview and documentation data collection techniques. Data validity uses triangulation which is then analyzed qualitatively. The research results show that (1) their disputes, according to Dean G. Pruitt and Jeffrey Z. Rubin's dispute theory, are caused by differences in interests and one of the effective resolution efforts is mediation. The implementation of this mediation resulted in an agreement to inherit; split property rights; and carry out a transfer of rights or change of name. (2) The successful implementation of mediation is in accordance with Lawrence M. Friedman's theory because it is supported by legal structure, legal substance, and legal culture. The strategy implemented is to ensure that disputes are resolved through mediation; coordinate with legal counsel; declare readiness to provide assistance; and communicate with the parties to the dispute.